Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan Kit Alat Percobaan Usaha dan Energi terhadap Penguasaan Konsep Fisika Peserta didik - Muhammad Tegar Septiaji Pramudyawan; Aris Doyan; Jannatin 'Ardhuha (Jurnal Penelitian Pendidikan IPA, 2020)
Abstract: This research purposed to examine the effect of guided inquiry learning using kit of work and energy experiment tools toward mastery of student physics concepts. This is quasi experiment research with posttest-only control group design. The population of this research is all students of class X MS SMAN 1 Kediri. The sampling technique used is random sampling, so selected the students of class X MS 1 as experiment group and X MS 2 as control group. The experiment group was treated with guided inquiry learning using kit of work and energy experiment tools and the control group was treated with conventional learning. The instrument used to measure concept of mastery is a test instrument in the form of a multiple-choice test of 25 questions. The research hypothesis was tested used t-test at the significance level 5%. The result of t-test showed that there was an effect of guided inquiry learning using kit of work and energy experiment tools toward mastery of student physics concepts. Keywords: Guided inquiry; kit of work and energy experiment tools; mastery of concept